Aksiologi Filsafat Ilmu dalam Pengembangan Keilmuan - Maria Sanprayogi; Moh. Toriqul Chaer (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
Humans develop a set of knowledge. This is predicated on the fact that he needs it. Because people inevitably have to determine for yourself how he behaved towards the prerequisites-a precondition of his life, and because the whole of reality is potentially took, he was in such need of accuracy and the overall integral knowledge of reality. Human beings can only live well when he responded to the reality of it as it is, and for that he should know, of the review historically, fitsafat was the one who originally handled the